Social Work's Program By Universitas Negeri Malang Spraying Desinfectant of Distribution of Covid-19 Trafficking Kunti District, Bungkal Ponorogo - Hikmah Fatimah; Ulinuha Mastuti Hafsah (Faculty of Education Universitas Negeri Malang, 2020)
Corona virus pandemic or Covid-19 that occurs in all countries in the world causes a decrease in various sectors in life. In a long period of time, no vaccine has been found to prevent transmission of the virus. This has inspired the Covid edition of social works program at Universitas Negeri Malang (State University of Malang) to make a breakthrough in preventing Covid-19 transmission. One of the work programs that showed a breakthrough in preventing Covid-19 transmission was spraying disinfectants in Kunti Village, Bungkal District, Ponorogo.Spraying of disinfectants is carried out 5x within a period of 45 days by using an electric sprayer with disinfectants and water solvents. Spraying disinfectants is expected to kill the virus that is developing in the body of bacteria that will die if exposed to disinfectants, so as to reduce the amount of ODP in the village of Kunti